ON THE TEACHING AND METHODOLOGICAL ASPECTS OF THE SPECIALIZED COURSE "PERSIAN LANGUAGE 5, 6" (Journal of Oriental Studies, 2025)
The article discusses several teaching and methodological features of the "Persian 5, 6" professional course. This course covers the Persian language levels B3 (Intermediate) and C1 (Advanced), designed for students of the Department of Iranian Studies at Yerevan State University, as well as those interested in these language levels. The thematic content and methodological approach of this professional course were developed by the Department of Iranian Studies for an Armenian-speaking audience, drawing from years of continuous teaching and conducted studies. Today, the growing necessity and widespread application of Persian present a challenge for language teachers, as this issue must be approached in new ways, with fresh perspectives, approaches, and proposals for innovative solutions to the challenges posed. The article aims to present the specific features of teaching the "Persian-5, 6" subject in the Armenian-language classroom, to improve the quality of learning the subject, and to develop and enhance the application of teaching methods and skills.
Keywords: "Persian language 5, 6"; professional course; B3 (intermediate); C1 (advanced); goals and objectives; teaching methods; educational outcomes